NEW MEDIA AND YOUTH’S ONLINE CIVIC ENGAGEMENT IN NIGERIAN POLITICS: POTENTIALS AND CHALLENGES - Chinwe Elizabeth Uzochukwu; Uche Patricia Ekwugha (European Scientific Journal, ESJ, 2014)
This paper focuses on the place of the new media in promoting online civic engagement among the Nigerian youths. Situated within the framework of the democratic-participation and the uses and gratifications theories of the media, the paper acknowledges that the new media possesses the potential to engender online civic engagement among the young people population through offering them a platform for acquiring information necessary for civic participation; for engaging in political discussions/debates in an atmosphere of enhanced freedom of speech; for direct conversations with elected representatives; for pushing for change; and for achieving group mobilisation. The paper, however, argues that before the new media could effectively perform these roles, certain factors must first be addressed and these include the extent of the youth’s interest in politics, the conduciveness (or helpfulness) of the political environment and the responsiveness of the government of the day to the civic engagement cause. Once these issues are properly sorted out, the paper believes, the potentials of the new media as a catalyst for youth online civic engagement would be better realised.